Odpowiedź :
Odpowiedź:
h) 7x-3= 2x+17
7x-2x= 17+3
5x= 20 /:5
x=4
spr.. 7*4-3= 2*4+17
28-3= 8+17
25= 25
L=P
i) x-5= 2x-20
x-2x= -20 +5
-x= -15 /*(-1)
x=15
spr.. 15-5= 2*15- 20
10= 30-20
10=10
L=P
j) 4x+5 = 2x -21
4x-2x= -21 -5
2x= -26 /:2
x= - 13
spr.. 4*(-13) +5= 2*(-13) -21
-52 +5= -26 -21
-47 = -47
L=P
k) 2x-3 +4x-6 = 20-x
2x +4x +x= 20 +3 +6
7x= 29 /:7
x= 29/7= 4 i 1/7
spr... 2*29/7 -3 + 4 *29/7 -6= 20 - 29/7
58/7 -3 + 116/7 -6= 20- 4 i 1/7
8 i 2/7 -3 -6 + 16 i 4/7= 19 i 7/7- 4 i 1/7
24 i 6/7 - 9= 15 i 6/7
15 i 6/7= 15 i 6/7
L=P
l) 7x-2x -4x =x+3x +12
7x-2x -4x -x-3x= 12
7x- 10x= 12
-3x= 12/:3
x= -4
spr.. 7 *(-4) -2*(-4) -4*(-4) = -4+3*(-4)+12
- 28 +8+16= - 4-12 +12
-28 + 24= - 4
-4=-4
L=P
Szczegółowe wyjaśnienie: